Classifying interval cancers as false negatives or newly occurring in fecal immunochemical testing. (September 2021) - Hsu, Wen-Feng; Hsu, Chen-Yang; Yen, Amy Ming-Fang; Chen, Sam Li-Sheng; Chiu, Sherry Yueh-Hsia; Fann, Jean Ching-Yuan; Lee, Yi-Chia; Chiu, Han-Mo; Chen, Hsiu-Hsi
Objective: To classify interval colorectal cancers as false negatives or newly occurring cases in a biennial Fecal immunochemical test (FIT) screening program and by various interscreening intervals. Setting: Data from the Taiwanese biennial colorectal cancer screening program involving FIT from 2004 to 2014 were used to estimate the incidence rate of asymptomatic colorectal cancer and the rate of its subsequent progression to clinical mode. Methods: The sensitivity of detecting asymptomatic colorectal cancers excluding newly developed colorectal cancers was compared to the conventional estimate of sensitivity, the complementary FIT interval cancer rate as a percentage of the expected incidence rate ((1-I/E)%). The relative contribution of newly developed or false-negative cases to FIT interval colorectal cancers was estimated by age and interscreening intervals. Results: The Taiwanese biennial fecal immunochemical test screening program had a conventional sensitivity estimate of 70.2%. After newly developed colorectal cancers were separated from FIT interval cancers, the ability to detect asymptomatic colorectal cancers increased to 75.5%. FIT interval colorectal cancers from the biennial program mainly resulted from newly developed colorectal cancers (68.8%). The corresponding figures decreased to 61.1% for the annual program but increased to 74.7% for the triennial program. The preponderance of newly developed colorectal cancers among FIT interval cancers was more prominent in screenees aged 50–59  than in those aged 60–69. Conclusions: Newly developed colorectal cancers showed a predominance among the FIT interval colorectal cancers in particular in the younger population screened. It is desirable to identify high-risk individuals to offer them a short interscreening interval or advanced detection methods to reduce their odds of developing interval cancer.